1998
DOI: 10.1007/bf02253354
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 long terminal repeat quasispecies differ in basal transcription and nuclear factor recruitment in human glial cells and lymphocytes

Abstract: The generation of genomic diversity during the course of infection has the potential to affect all aspects of HIV-1 replication, including expression of the proviral genome. To gain a better understanding of the impact of long terminal repeat (LTR) sequence diversity on LTR-directed gene expression in cells of the central nervous system (CNS) and immune system, we amplified and cloned LTRs from proviral DNA in HIV-1-infected peripheral blood. Sequence analysis of nineteen LTRs cloned from 2 adult and 3 pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In this regard, only AP-1 expressed in glial and HeLa cells, but not in Jurkat and neuronal cells, was reported to interact with the HIV-1 LTR (68). These findings suggest that distinct forms of this transcription factor possess different binding capacities for HIV DNA as well as differential potency in modulating HIV transcription (68,69). Indeed, certain members of the Jun and Fos families may exert suppressive effects on viral transcription, as previously described with cAMP-responsive element (CRE)/ATF in Jurkat and HeLa cells (70).…”
Section: Discussionmentioning
confidence: 79%
“…In this regard, only AP-1 expressed in glial and HeLa cells, but not in Jurkat and neuronal cells, was reported to interact with the HIV-1 LTR (68). These findings suggest that distinct forms of this transcription factor possess different binding capacities for HIV DNA as well as differential potency in modulating HIV transcription (68,69). Indeed, certain members of the Jun and Fos families may exert suppressive effects on viral transcription, as previously described with cAMP-responsive element (CRE)/ATF in Jurkat and HeLa cells (70).…”
Section: Discussionmentioning
confidence: 79%
“…1A). Previous studies have indicated that sequence variation at the ATF/CREB site impacts ATF/CREB protein binding and HIV-1 LTR activity (22,23). Furthermore, numerous reports have described synergistic transactivation of different promoters by proteins from the ATF/CREB and C/EBP families (33,35,41).…”
Section: Identificationmentioning
confidence: 99%
“…1A. In this report, the functional properties of C/EBP binding site I are examined along with the impact of a directly adjacent ATF/CREB site (22,23) on the activity of this NF-B-proximal cis-acting element relevant to LTR-directed transcription in cells of the monocyte/macrophage lineage.…”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancer region is located upstream of the GC box array and consists of two tandem nuclear factor-κB (NF-κB) binding sites. The modulatory region, located further upstream of the NF-κB sites, includes binding sites for CCAAT/enhancer binding proteins (C/EBP), activating transcription factor/cyclic AMP response element binding (ATF/CREB) factors, lymphocyte enhancer factor (LEF-1), nuclear factor of activated T cells (NFAT), and a number of other transcription factors [3,4].…”
Section: Introductionmentioning
confidence: 99%